The cat who came to breakfast - Braun, Lilian Jackson (Jove Books, 1995)
The development of a major resort at the south end of Breakfast Island is causing a ruckus. Local residents, summer people, and mainland fishermen are all hopping mad that the peace of their island retreat is being shattered. Then a cabin cruiser explodes in the marina, causing general alarm. But when a series of deadly "accidents" follows on the heels of the mysterious explosion, Qwilleran begins to wonder if sabotage is involved.